Analysis of eutrophication levels in the Mediterranean Lagoons (Cabras and Santa Giusta) of Italy trough chlorophyll using multi-resolution images and temporal observation - Ashish, Kamana; Virdis, Salvatore G. P.; Tripathi, Nitin Kumar; Miyazaki, Hiroyuki; Padedda, Bachisio Mario; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Eutrophication of the 2 Mediterranean coastal lagoons was the issue considered in this study. This problem gets more intense through the nutrient input from surrounding places which dispose their waste into the considered water body, which resists the oxygen from entering into water body by forming algal blooms on top layer of lake and the bacteria to decompose algae it makes the water body anoxic. Literature suggests that the most common methods used for the empirical equation and semi analytic methods. And for empirical equation, 2B and 3B band models are used, based on their sensitivity to Chlorophyll. The bilinear interpolated values of the pixels are extracted because there are many chances of change in location due to different parameters. The temperature also has an effect on the eutrophication. All the environment related issues leading eutrophication are studied. This issue was analyzed using different satellite images and their distinct band combinations using linear regression between the field chlorophyll and TOA reflectance. The maps are generated by giving TOA bands (Red and NIR combination) as a input along with m and q values in the linear regression equation. Temperature from Landsat 8 has been extracted for only Cabras due to its available images. This method yielded to give average kind of results when compared the field data with the entire dataset but yielded good results when done individually. Specifically, the Red and NIR band combination yielded most number of good results. The seasonal behavior of both the lakes are not similar though they are located proximally low distant to each other. The Land Surface temperature estimated through Landsat 8, yielded great outcomes when related to the field temperature information.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Remote Sensing and Geographic Information System, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2018
Keywords: Eutrophication -- Control -- Italy -- Mediterranean Sea; Three-dimensional imaging -- Italy -- Mediterranean Sea; Chlorophyll